Entry and Exit Policy and Ties with University as Critical Success Factors Influencing Agri-Business Incubation Performance (Global Journal of Management and Business Research, 2018)
Business incubation performance is linked to many key factors. This study is focusing on two factors, namely Entry and Exit Policy and Ties with University. The effort is to understand that are these Critical success factors influencing Agri-Business Incubation performance. Through literature review the constructs for Entry and Exit Policy was 0.730; for Ties with University, it was designed. The reliability score for all three constructs was above the threshold value of 0.70. Entry and Exit Policy factor had Cronbach alpha of 0.730; for Ties with University it was 0.933 and for Business Incubation (BI) Performance it was 0.703. Factor analysis was conducted for Entry and Exit Policy factors and it helped to reduce the seven items to three, viz. i) EE11: Applicant's proposal potentiality; ii) EE12: Admission & Graduation policy; and iii) EE13: Post incubation scenario. These three factors explained 81.378 percent of the variance. A model depicting relation of SEM-PLS was Entry and Exit Policy and Ties with University was designed to understand the criticality of these factors. Results suggest that both Entry and Exit Policy factors and Ties with University emerged as significant predictors of BI performance. They explained 49.2 percent of the variation. This study thus highlights that entry and exit policy and Ties with University emerge as important predictors of agri-BI performance.